Combining superselective catheterization and electrochemotherapy: A new technological approach to the treatment of high-flow head and neck vascular malformations - Krt, Aljosa; Cemazar, Maja; Lovric, Dimitrij; Sersa, Gregor; Jamsek, Crt; Groselj, Ales (Frontiers in Oncology, 2022)
Introduction The study aims to demonstrate a combination of superselective catheterization and electrochemotherapy as a feasible and effective new technological approach in treating high-flow vascular malformations of the head and neck region. Patients and methods In the patient with high-flow arteriovenous malformation of the lower lip, superselective catheterization was performed under general anesthesia. The microcatheter was used to administer 750 IU BLM intra-arterially into the feeding vessel. The whole malformation surface was then covered with 15 applications of electric pulses using the plate electrode. Results Excellent response, without functional or aesthetic deficits, was obtained in 10 weeks. During this period, debridement and necrectomy were performed regularly on follow-up visits. The pain was managed with oral paracetamol and sodium metamizole. Conclusion Combining electrochemotherapy using bleomycin with superselective catheterization and arteriography is a feasible treatment option for high-flow vascular malformations in the head and neck region and could play a significant role in managing these challenging lesions.